Mahtematics evolution in the Universidad Nacional de Trujillo: My life experience with mathematics - Ortiz Fernández, Alejandro (2020)
To describe our academic-professional life in the UNT during the period of 1960 - 1989 (february)- To leave a legacy to the present and future generations.